2020
DOI: 10.1002/app.49136
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cure characteristic, physico‐mechanical, and dielectric properties of calcium copper titanate filled acrylonitrile‐butadiene rubber composites: Effect of calcium copper titanate loading

Abstract: Calcium copper titanate (CCTO) has been synthesized by high temperature solid‐state reaction from calcium carbonate, copper (II) oxide, and titanium dioxide as the starting materials. The formation and morphology of CCTO were confirmed by X‐ray diffraction, Fourier‐transformed infrared spectrophotometry, scanning electron microscopy (SEM), and particle size analysis. In order to develop flexible dielectric materials, acrylonitrile‐butadiene rubber (NBR)‐based composites were prepared with CCTO content varied f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…In other words, the composites (ENR1.5 and ENR5) appear to phase separate and have less filler-polymer interaction compared to neat ENR. 42 As expected, it is found that tanδ max of ENR1.5 is slightly lower than that of ENR5. T g slightly shifts to a higher value than that of ENR5.…”
Section: Dynamic Mechanical Analysissupporting
confidence: 74%
See 1 more Smart Citation
“…In other words, the composites (ENR1.5 and ENR5) appear to phase separate and have less filler-polymer interaction compared to neat ENR. 42 As expected, it is found that tanδ max of ENR1.5 is slightly lower than that of ENR5. T g slightly shifts to a higher value than that of ENR5.…”
Section: Dynamic Mechanical Analysissupporting
confidence: 74%
“…With KCNO loading, the tensile strength and elongation at break decrease, showing that the filler was unable to transfer stress of the rubber matrix. 42 However, the ENR1.5 specimen shows a slightly higher tensile strength than ENR0.5. These results are supported by E′ and tan δ max of ENR 1.5, which are lower than ENR5, as previously discussed.…”
Section: Resultsmentioning
confidence: 93%
“…The possible shortcoming of employing CCTO at higher concentration was the agglomeration of the particles that led to a compromise in the mechanical properties of the resulting DE. [ 85 ] In addition, ferrite fillers (spinel ferrites) were also observed to be promising candidate for the fabrication of dielectric rubber composites. Spinel ferrites are also employed with both natural and synthetic rubbers, namely styrene butadiene styrene (SBR), ethylene propylene diene rubber (EPDM), etc.…”
Section: Nitrile Butadiene Rubber (Nbr) As Dielectric Elastomermentioning
confidence: 99%
“…Several attempts have been made to synthesize materials with a dielectric constant in broad ranges of temperatures and frequencies. Other applications, including the synthetic rock used for storing nuclear waste and for various catalytic applications like partial oxidation of light hydrocarbons [86][87][88]. Luangchuang et al reported improved flexible dielectric materials using polar NBR as the matrix owing to its high dielectric constant, processability, and thermal resistance.…”
Section: Applicationsmentioning
confidence: 99%